Investment policies and telecommunications regimes - Zdenek Drabek (Hamburg Institute of International Economics (HWWA), 2002)
This paper looks at the role of the key international agreements in the process of liberalization of the telecommunications industry. We analyse in particular the role of the WTO agreement in furthering liberalization around the world, and the extent to which it provides protection for foreign investors. The analysis includes assessments of not only market access but also the treatment of property rights, rights of way, financial conditions and regulations as well as issues related to market structure and competition. Outstanding issues representing impediments of these agreements are also identified. The approach is to a large extent based on a comparison with other relevant international agreements, especially with NAFTA. The WTO agreement comes out of the analysis quite well. It is an important instrument of protecting and safeguarding market access for foreign investors even though, undoubtedly, several areas of the agreement will be subject to pressures for further negotiations. – – Dieses Papier befasst sich mit der Rolle der bedeutendsten internationalen Abkommen im Liberalisierungsprozess der Telekommunikation. Speziell fragen wir nach dem Beitrag des WTO-Abkommens zur weltweiten Liberalisierung und nach dem Schutz, den es ausländischen Investoren gewährt. Die Analyse umfasst die Beurteilung der Regelungen über Marktzugang, Eigentumsrechte, Wegerechte, finanzielle Bedingungen und Regulierungen sowie Fragen der Marktstruktur und des Wettbewerbs. Ferner werden die noch offenen Probleme behandelt. Der Ansatz beruht in einem erheblichen Maße auf einem Vergleich mit anderen relevanten internationalen Abkommen, insbesondere NAFTA. Das WTO-Abkommen schneidet bei dieser Untersuchung recht gut ab. Es ist ein bedeutendes Instrument zur Sicherung des Marktzugangs für ausländische Anbieter, auch wenn zu erwarten ist, dass für Teile des Abkommens Druck zur Aufnahme weiterer Verhandlungen entstehen wird.
Keywords: F02; F13; L96; 330; International Economic Order; WTO; NAFTA; Trade Negotiations; International Investment; Telecommunications Services; Telekommunikationspolitik; Internationaler Dienstleistungsverkehr; WTO-Regeln; Telekommunikation; Direktinvestition; Investitionsgarantie; Investitionspolitik; Welt